PROFIL ANTROPOMETRIK, VITAMIN D, B12, FOLAT, DAN FERITIN PASIEN OBES PRABEDAH BARIATRIK DI POLIKLINIK GIZI RUMAH SAKIT SUMBER WARAS - Anastasia Hayuningtyas; Lady Dhita Alfara; Tjandraningrum; Victor Tambunan; Lukman Halim; Meilani Kumala; Johana Titus (Perhimpunan Dokter Gizi Klinik Indonesia, 2023)
Obese patients, especially patients with severe obesity and requiring bariatric surgery, have a high prevalence of nutrient deficiencies. This study aims to determine some of the basic characteristics of patients undergoing bariatric surgery so that they can be used as supporting data for post-bariatric surgery nutrition medical therapy, particularly in the provision of food sources and micronutrient supplementation which can be deficient due to anatomic and physiological alterations after the surgery. The study was conducted on 55 preoperative bariatric patients by assessing age, gender, and degree of obesity based on body mass index (BMI), serum vitamin D and B12 levels, erythrocyte folic acid, and serum ferritin of subjects. The study is descriptive with a cross-sectional design. Subjects were taken by consecutive sampling. The results showed that the mean age of preoperative bariatric patients was 36 ± 7.1 years; most (85.5%) were women. Most subjects (34.5%) had BMI of 35–39.9 kg/m2. Vitamin D deficiency was present in most (75.6%) of the study subjects, but most had serum vitamin B12 levels, erythrocyte folic acid levels, and serum ferritin levels within normal limits. This study shows that the basic profile of patients undergoing bariatric surgery is primarily late adults, classified as severe obese and having vitamin D deficiency. Keywords: Obesity, Prebariatric, Serum Vitamin D, Serum Vitamin B12, Erythrocyte Folic Acid, and Serum Ferritin.